POTENSI EKOWISATA DANAU UTER DI DISTRIK AITINYO KABUPATEN MAYBRAT-PAPUA BARAT DAYA - Sepus Fatem; Jonni Marwa; Marlin Bosawer (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
The research was conducted on Danau Uter, at Aitinyo District of Maybrat Regency. The aim of this study was to find out 1) the existence of Danau Uter as ecotourism object to support economic condition of society, 2) social culture condition and the supporting of local government in ecotourism development and 3) inspect the supporting factors in ecotourism development. The method used are descriptive analyse and study case. Data collected were tourism object, social culture of local society, accessibility, accommodation, infrastructure and the encouraging of government. The result shows that Danau Uter is reasonable to become an ecotourism object which supported by beautiful panorama, historical sites, fauna and flora biodiversity, social culture condition of local society and supporting infrastructure. On the other hand, local government is yet very supportive of ecotourism development.